2011
DOI: 10.1124/mol.110.070409
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Induced Silencing Complex-Bound Small Interfering RNA Is a Determinant of RNA Interference-Mediated Gene Silencing in Mice

Abstract: Deeper knowledge of pharmacokinetic and pharmacodynamic (PK/PD) concepts for RNA therapeutics is important to streamline the drug development process and for rigorous selection of best performing drug candidates. Here we characterized the PK/PD relationship for small interfering RNAs (siRNAs) targeting luciferase by examining siRNA concentration in plasma and liver, the temporal RNA-induced silencing complex binding profiles, mRNA reduction, and protein inhibition measured by noninvasive bioluminescent imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 41 publications
1
51
1
Order By: Relevance
“…A strong in vitro and in vivo correlation was seen in the relationship between the number of siRNA molecules per cell and mRNA knockdown (Figure 3a, b). Although these results were different from the fact that the Argonaute 2 (Ago2)-bound siRNA fraction, but not the total amount of siRNA found in the liver were correlated with target mRNA inhibition [11], we speculate that the capacity of siRNA to bind Ago2 was not saturated at our doses. The other possible explanation may be that most of the siRNAs in the cytosol are present in condensed form.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…A strong in vitro and in vivo correlation was seen in the relationship between the number of siRNA molecules per cell and mRNA knockdown (Figure 3a, b). Although these results were different from the fact that the Argonaute 2 (Ago2)-bound siRNA fraction, but not the total amount of siRNA found in the liver were correlated with target mRNA inhibition [11], we speculate that the capacity of siRNA to bind Ago2 was not saturated at our doses. The other possible explanation may be that most of the siRNAs in the cytosol are present in condensed form.…”
Section: Discussioncontrasting
confidence: 46%
“…We initially focused on the PD, which can be analyzed based on the relationship between the number of cytosolic siRNA molecules and its gene silencing activity, because previous reports suggested that PD contributed to the non-linear relationship in both pDNA and siRNA delivery systems [8][9][10][11]. In this study, the number of siRNA molecules in the cells was used to estimate PD of siRNA.…”
Section: Analysis Of a Pd Between In Vitro And In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…This is the reason that total siRNA in tissues does not always generally agree with efficacy Seitzer et al 2011). Wei et al (2011 demonstrated that target mRNA silencing in LNP-siRNA-treated livers correlated with the amount of siRNA bound to Ago2 but not with the siRNA measured in total liver lysates.…”
Section: Analyses Of Sirna Endosomal Escape and Riscloaded Sirnamentioning
confidence: 99%
“…Therefore, as highlighted in a recent PK/PD relationship study by Wei et al (2011), high concentrations of siRNA at the desired target organ do not necessarily correlate with a high knock-down level of the desired mRNA. Factors that are also likely to be needed for successful RNAi are as follows: number of Ago2-siRNA complexes, turnover of the Ago2 complex, stability of the siRNA, target mRNA half-life, mRNA expression levels, cell division and turnover, or a combination thereof.…”
Section: Adme Properties Of Lnp-formulated [ 3 H]-sirnamentioning
confidence: 99%